Application of digitalization in legal science and legal proceedings of modern Uzbekistan: Theoretical and legal analysis - Firuza, Mukhitdinova (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The purpose of participation at the conference with the article is to reveal the significance and relevance of the problems of the implementation of human rights in the context of the digitalization of society and the development on this basis of evidence-based recommendations, effective mechanisms aimed at the effective protection of human rights and freedoms in modern Uzbekistan. The author paid attention to the implementation of an individual approach, real access to any Internet resources necessary for the educational process, and training in virtual laboratories, in classrooms. Having studied foreign experience, thanks to digitalization, it is possible to select and adapt the content of education and teaching methods, consolidating educational material in accordance with the needs and capabilities of students and the tasks set by a modern teacher. The author considers the legal framework that regulates this process, as well as a theoretical, historical, and legal analysis of digitalization, a comparative and scientific study of current trends in the use of digital technologies in human life based on the study of foreign and national experience.